2012
DOI: 10.1007/s13361-012-0473-0
|View full text |Cite
|
Sign up to set email alerts
|

Electron Capture Dissociation of Disulfide, Sulfur–Selenium, and Diselenide Bound Peptides

Abstract: To examine the electron capture dissociation (ECD) behavior of disulfide (S-S), sulfur-selenium (S-Se), and diselenide (Se-Se) bonds-containing peptides, a series of free cysteine (Cys) and selenocysteine (Sec) containing peptides were reacted to form interchain S-S, S-Se, and SeSe bonds, and then studied using ECD with Fourier transform ion cyclotron mass spectrometry (FTICR MS). These results demonstrate that the radical has higher tendency to stay at selenium rather than sulfur after the cleavage of Se-S bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 41 publications
0
17
0
1
Order By: Relevance
“…In odd‐electron based tandem mass spectrometry methods such as ECD, ETD, and EDD, it has been widely observed that the disulfide bond is readily cleaved (Zubarev et al, ; Chrisman et al, ; Kalli & Håkansson, ; Wu et al, ; Cole et al, ; Li & O'Connor, ). Likewise, in radical‐based tandem mass spectrometry, disulfide bonds are selectively cleaved (Lee et al, ; Tan & Xia, ).…”
Section: Fragmentation Characterisitcsmentioning
confidence: 99%
“…In odd‐electron based tandem mass spectrometry methods such as ECD, ETD, and EDD, it has been widely observed that the disulfide bond is readily cleaved (Zubarev et al, ; Chrisman et al, ; Kalli & Håkansson, ; Wu et al, ; Cole et al, ; Li & O'Connor, ). Likewise, in radical‐based tandem mass spectrometry, disulfide bonds are selectively cleaved (Lee et al, ; Tan & Xia, ).…”
Section: Fragmentation Characterisitcsmentioning
confidence: 99%
“…Directly below sulfur in the periodic table is selenium. Sulfur and selenium are known to have similar physical and chemical properties [27][28][29]. Although there are similarities between sulfur and selenium, their antioxidant mechanisms differ in preventing oxidative cellular damage [4,30].…”
Section: Introductionmentioning
confidence: 99%
“…The typical symbol for such anionic systems is (RX.˙.XR) •‐ in which X denotes S, Se, N, P, and so on and R denotes Ph, CH 3 , and other functional groups . Electron capture dissociation (ECD) with Fourier transform ion cyclotron mass spectrometry (FTICR MS) has been used for direct measurement of sulfur and selenium centered 2c‐3e bond complexes …”
Section: Introductionmentioning
confidence: 99%
“…Optical absorption spectra, and in particular the position of λ max and lifetimes ( t 1/2 ) of these bands may be used to provide indirect information on the nature and strength of 2c‐3e bonds of these complexes. Characterization of 2c‐3e bond in cyclic dithia radical cations, pepetides, azoalkanes, transition metal complexes, and other sigma bonded radical cationic complexes through optical absorption spectroscopy are reported in the literature. Absorption maximum ( λ max ) is described to correspond the energy gap between the doubly occupied σ bonding orbital and singly occupied σ* antibonding orbital and this is often being correlated to the strength of a 2c‐3e ‐S∴S‐ bond.…”
Section: Introductionmentioning
confidence: 99%